Silent Witness: Dual-Species Transcriptomics Reveals Epithelial Immunological Quiescence to Helminth Larval Encounter and Fostered Larval Development - Ebner, Friederike; Kuhring, Mathias; Radonić, Aleksandar; Midha, Ankur; Renard, Bernhard Y.; Hartmann, Susanne (Frontiers in Immunology, 2018)
Gastrointestinal nematodes are amongst the most prevalent parasites infecting humans and livestock worldwide. Infective larvae of the soil-transmitted nematode Ascaris spp. enter the host and start tissue migration by crossing the intestinal epithelial barrier. The initial interaction of the intestinal epithelium with the parasite, however, has received little attention. In a time-resolved interaction model of porcine intestinal epithelial cells (IPEC-J2) and infective Ascaris suum larvae we addressed the early transcriptional changes occurring simultaneously in both organisms using dual-species RNA-Seq. Functional analysis of the host response revealed an overall induction of metabolic activity, without induction of immune responsive genes or immune signaling pathways and showing suppression of chemotactic genes like CXCL8/IL-8 or CHI3L1. Ascaris larvae, when getting in contact with the epithelium, showed induction of genes that orchestrate motor activity and larval development, such as myosin, troponin, myoglobin and protein disulfide isomerase 2 (PDI-2). In addition, excretory-secretory products that likely facilitate parasite invasion were increased, among them aspartic protease 6 or hyaluronidase. Integration of host and pathogen data in an inter-species gene co-expression network indicated links between nematode fatty acid biosynthesis and host ribosome assembly/ protein synthesis. In summary, our study provides new molecular insights into the early factors of parasite invasion, while at the same time revealing host immunological unresponsiveness. Reproducible software for dual RNA-Seq analysis of non-model organisms is available at https://gitlab.com/mkuhring/project_asuum and can be applied to similar studies.